Membangun Kesadaran Santripreneur Berbasis Kearifan Lokal di Pondok Pesantren - Zamroni, Zamroni; Baharun, Hasan; Febrianto, Achmad; Ali, Muhammad; Rokaiyah, Siti (Al-Tijary, 2022)
Information technology has affected society, especially entrepreneurship. Smart millennials must be taught to look for opportunities to maximize technology use. Entrepreneurship basics must be understood by the trained age. For poverty reduction, pesantren economic empowerment is developed to improve the community's economy. Due to the pesantren's economic urgency, various activities can revive its economy and foster student entrepreneurship. At Nurul Jadid Islamic Boarding School, students are taught to be entrepreneurs. This study aims to analyze and understand the activities carried out by the Nurul Jadid Islamic Boarding School to raise awareness of santripreneurs based on local wisdom. This study uses a qualitative approach to the type of phenomenology, in which researchers try to find and understand the phenomena that exist and are developing at this time. The data collection technique was carried out using participant observation, interviews with several informants, and documentation. Data analysis is done by presenting, collecting, and drawing conclusions. The results showed that building students' awareness of the importance of entrepreneurship was carried out by the Nurul Jadid Islamic Boarding School Community through Skills Activities carried out by bringing in mentors, Opening of Bazaar Stands, and Pesantren Cooperatives. This research affects Islamic boarding schools' role in empowering local wisdom-based economies.